DeLee & Drez's orthopaedic sports medicine principles and practice - DeLee, Jesse; Drez, David; Miller, Mark D. (Saunders, 2002)
Covering all athletes from children to adults, this 2-volume reference explores the diagnosis and treatment of the full spectrum of sports-related injuries, training, medical disorders, and the basic sciences. It provides the most clinically focused, comprehensive guidance available in any single source, with contributions from the most respected authorities in the field.